Sensitivity and specificity of a quick sequential [Sepsis‐Related] organ failure assessment sepsis screening tool. Issue 12 (25th September 2021) - Alberto, Laura; Marshall, Andrea P.; Walker, Rachel M.; Pálizas, Fernando; Aitken, Leanne M.
Abstract: Aim: There is limited evidence on the diagnostic accuracy of a quick Sequential [Sepsis‐Related] Organ Failure Assessment (qSOFA) sepsis screening (SS) tool in developing nation health settings. The aim of this study was to test the diagnostic accuracy of a qSOFA‐based SS tool, and the predictive validity of the qSOFA score in hospital ward patients from Argentina. Methods: Prospective observational study. Patients (≥18 years, without sepsis) were recruited within 24‐48 hours of admission to a 169‐bed tertiary referral private hospital in Buenos Aires. The index test was the qSOFA‐based SS tool, and the reference standard sepsis diagnosed at discharge blindly evaluated with reference to the Sepsis‐3. Results: In 1151 patients (median age 69.9 [IQR, 29.0]); 47 (4.1%) had sepsis, 413 (35.9%) had infection and 691 (60.0%) other diagnoses at discharge. The qSOFA‐based SS tool (index test) had moderate sensitivity (60%), good specificity (89%), a very low positive (19%) and very high negative (98%) predictive value for sepsis diagnosed at discharge according to the Sepsis‐3 criteria (reference standard). For the same outcome, the qSOFA score in isolation had a reasonable predictive validity area under receiver operating characteristics curve 0.77 (95% CI 0.70‐0.83) P < 0.001. Conclusion: The qSOFA score could reasonably discriminate patients at risk of developing sepsis; qSOFA‐based screening may be valuable where no screening criteria are in place.